PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMAN 4 PRAYA PADA MATERI LAJU REAKSI TAHUN PELAJARAN 2019/2020 - Watoni, Muh.; Savalas, Lalu Rudyat Telly; Muti'ah, Muti'ah (Jurnal Ilmiah Pendidikan Indonesia, 2021)
The aim of this research was to know the effect of problem-based learning on study outcome of student in class XI IPA SMAN 4 praya on reaction rate in the academic year of 2019-2020. This research assumed a semi-experimental approach. The design of this research was pre-test post-test nonequivalent control group. The population of this research were all students of XI IPA SMAN 4 Praya which amounted to 216 students. The samples was taken by using purposive sampling in which students of XI MIPA-4 became experimental class and XI MIPA-5 became the control class. An essay test was used to know study outcome of studentst. Student test data were analyzed by using independent t-test at significant level of 5%. The hypothesis test shows that implementation of problem based learning gives a positive and significant effect of study outcome of students in class XI MIPA SMAN 4 praya on reaction rate topic in the academic year of 2019-2020.